2010
DOI: 10.1007/s00421-010-1544-1
|View full text |Cite|
|
Sign up to set email alerts
|

Mitochondrial gene expression in elite cyclists: effects of high-intensity interval exercise

Abstract: Little is known about the effect of training on genetic markers for mitochondrial biogenesis in elite athletes. We tested the hypothesis that low-volume sprint interval exercise (SIE) would be as effective as high-volume interval exercise (IE). Ten male cyclists competing on national elite level (W (max) 403 ± 13 W, VO(2peak) 68 ± 1 mL kg(-1) min(-1)) performed two interval exercise protocols: 7 × 30-s "all-out" bouts (SIE) and 3 × 20-min bouts at ~87% of VO(2peak) (IE). During IE, the work was eightfold large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 51 publications
3
14
0
1
Order By: Relevance
“…Similarly, only SIE, and not CE, increased nuclear PGC-1α protein content post-exercise. Although the differential response to SIE and CE may be due to differences in the degree and time course of nuclear p53 and PGC-1α protein accumulation, our findings suggest that SIE may represent a more potent stimulus than CE to induce some of the early molecular events associated with mitochondrial biogenesis, as previously suggested31. An additional novel finding was that the exercise-induced increase in the nuclear content of p53 protein in human skeletal muscle was also accompanied by an increase in the nuclear content of PHF20, a protein that stabilises and activates p5329, but was not differentially regulated by the two types of exercise investigated.…”
Section: Discussionsupporting
confidence: 66%
“…Similarly, only SIE, and not CE, increased nuclear PGC-1α protein content post-exercise. Although the differential response to SIE and CE may be due to differences in the degree and time course of nuclear p53 and PGC-1α protein accumulation, our findings suggest that SIE may represent a more potent stimulus than CE to induce some of the early molecular events associated with mitochondrial biogenesis, as previously suggested31. An additional novel finding was that the exercise-induced increase in the nuclear content of p53 protein in human skeletal muscle was also accompanied by an increase in the nuclear content of PHF20, a protein that stabilises and activates p5329, but was not differentially regulated by the two types of exercise investigated.…”
Section: Discussionsupporting
confidence: 66%
“…Two additional coactivators of mitochondrial biogenesis are PRC [33] and PGC-1β [34] . Acting in a similar manner to PGC-1α, PRC expression is increased with endurance exercise [35] , [36] and enhanced when performed concurrently with resistance exercise [37] . To the contrary, chronic endurance exercise appears to attenuate resting PGC-1β protein content [38] though acute exercise does not affect mRNA values [39] .…”
Section: Discussionmentioning
confidence: 97%
“…In addition, regulation at the mRNA level importantly contributes to the acute response and chronic adaptations to exercise. A large number of studies have shown that acute exercise induces genes involved in a variety of processes, including energy metabolism, hypertrophy and signalling [13], [14], [15], [16], [17], [18], [19], [20], [21]. Whole genome mRNA profiling has confirmed these findings, revealing major changes in skeletal muscle gene expression from 1 hour to even 48 hours after cessation of exercise [22], [23], [24], [25].…”
Section: Introductionmentioning
confidence: 95%